Environmental tobacco smoke exposure and periodontitis prevalence among nonsmokers in the hispanic community Health Study/Study of Latinos. Issue 2 (15th December 2016) - Akinkugbe, Aderonke A.; Sanders, Anne E.; Preisser, John S.; Cai, Jianwen; Salazar, Christian R.; Beck, James D.
Abstract: Objective: To describe self‐reported exposure to environmental tobacco smoke (ETS) and its association with periodontitis prevalence in a diverse group of Hispanics/Latinos. Methods: Data came from 8675 lifetime nonsmokers in the 2008–2011 Hispanic Community Health Study/Study of Latinos. Exposure to ETS was self‐reported, while periodontitis was defined using the Centers for Disease Control and Prevention‐American Academy of Periodontology criteria and the proportion of sites affected by clinical attachment level of ≥3 mm or pocket depth of ≥4 mm. Survey logistic regression estimated prevalence odds ratios (POR) and 95% confidence intervals (CI). In addition, we assessed whether greater hours of exposure to ETS in the past year was associated with greater periodontitis prevalence, and lastly, we conducted a simple sensitivity analysis of ETS misclassification. Results: Age‐standardized prevalence estimates (95% CI) for ETS exposure and periodontitis were 57.6% (55.9, 59.4) and 39.8% (38.1, 41.4), respectively. After adjusting for confounders and periodontitis risk factors, we estimated an overall adjusted POR (95% CI) for the ETS–periodontitis association as 1.09 (0.95–1.26) with a confidence limit ratio (CLR) of 1.34. This association varied in magnitude by Hispanic/Latino background, ranging from 1.04 (0.75, 1.43 with a CLR = 1.91) among Central Americans to 1.76 (1.16, 2.66 with a CLR = 2.29) in Puerto Ricans. Conclusions: Previously reported associations between ETS and periodontitis appear weak in this study. However, the magnitude of the association differs according to Hispanic/Latino background.